Exact Solution of Convective Mass Transfer Model for Calcium Response of Endothelium - Kumar V.; Pandey R.N.; Upadhyay S.N. (My University, 2025)
An exact solution for the concentration profile in tubes with surface reaction coupled with permeation have been obtained in terms of fast converging confluent hypergeometric function that gives accurate results. An excellent agreement between the experimental and theoretical results of the intracellular calcium ion concentration in the calf aorta endothelial cells and the extracellular ATP concentration provides yet another example in support of the mass transfer model for intracellular calcium response of the endothelial cells.